2007
DOI: 10.1159/000098562
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Behavioral versus Cognitive Measures in Differentiating between Subtypes of Frontotemporal Lobar Degeneration and Alzheimer’s Disease

Abstract: We hypothesized that a modified version of the Frontal Behavioral Inventory (FBI-mod), along with a few cognitive tests, would be clinically useful in distinguishing between clinically defined Alzheimer’s disease (AD) and subtypes of frontotemporal lobar degeneration (FTLD): frontotemporal dementia (dysexecutive type), progressive nonfluent aphasia, and semantic dementia. We studied 80 patients who were diagnosed with AD (n = 30) or FTLD (n = 50), on the basis of a comprehensive neuropsychological battery, ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 112 publications
1
27
1
2
Order By: Relevance
“…Performance on Trail Making Part B requires cognitive flexibility and set shifting, faculties thought to be impaired in FTD. 32 PPA subjects also declined on Trail Making, which again, may reflect the verbal nature of the test, or executive function deficits which may conceivably also emerge in this group given the overlap between these 2 syndromes over time.…”
Section: Discussionmentioning
confidence: 89%
“…Performance on Trail Making Part B requires cognitive flexibility and set shifting, faculties thought to be impaired in FTD. 32 PPA subjects also declined on Trail Making, which again, may reflect the verbal nature of the test, or executive function deficits which may conceivably also emerge in this group given the overlap between these 2 syndromes over time.…”
Section: Discussionmentioning
confidence: 89%
“…The test consists in ordering cards following one criterion; then the criterion changes and the patient must adapt to order the cards following the new criterion. The Trail Making Test, which consists in ordering one succession of numbers and one succession of letters and alternating numbers and letters, is also commonly used for the diagnosis of FTD [70,71]. …”
Section: The Ftd Symptoms and Corresponding Tests In Micementioning
confidence: 99%
“…In contrast, a number of other studies have reported severe executive deficits in nfvPPA as measured by the WCST or Trail Making Test Part B (Knibb et al, 2009; Nestor et al, 2003). Further, the executive problems in subjects with nfvPPA have been sometimes shown to be of a greater magnitude than in bvFTD (Heidler-Gary et al, 2007). Variable disease severity is certain to contribute to the discrepancy across studies, and it is also likely that cognitive profiles differ on a case by case basis.…”
Section: Executive Functioning In the Diagnosis Of Ftd Syndromesmentioning
confidence: 99%